De Revolutionibus - Franz Josef Brüseke (Ciências Sociais Unisinos)
During almost a century, the German social democracy provided the blueprint for the dispute between internal factions with consequences for some western parties until today. In the last decade of the nineteenth century the social democratic field was divided into ideological strands that go from one moderate-wing approach, that favored the political work of small steps within the law, bypassing the so called center-Marxist with a majority in the presidency of Social Democratic Party, to even more activists' groups, which defended a "revolutionary" break with bourgeois society as such. This moderate party had strong affinities with the syndicalism, allying itself with some intellectuals, who challenged the "Marxist" rhetoric of the social democratic party with reformist and revisionists' ideas. We draw attention to this constellation of ideological conflict within the German "Left" more than one hundred years ago, because it provides the matrix of the disputes and struggles within and between "left" parties during almost the entire twentieth century. In the center of the dispute we found a concept, the revolution.